Wakaf dan Politik di Tunisia - Budi Juliandi (AHKAM : Jurnal Ilmu Syariah, 2015)
For some experts, Tunisia is tended to be the most progressive, liberal and radical among other Islamic countries in the world, particularly in addressing the issues of women's rights and the prohibition of polygamy. However, development in the areas of family law is not followed by progress in other fields, mainly in the development of waqf.  For this case, Tunisia is the most underdeveloped compared to other Muslim countries, such as Saudi Arabia, Egypt, Pakistan, Bangladesh, Sri Lanka, Jordan, Brunei Darussalam, Malaysia, and Indonesia; even though, around the 19th century, the contribution of waqf land of Tunisia in 1883 had reached 1/3 of the entire ownership of the land. Currently, Tunisia Tunisia do not yet have the institutions and the laws governing the waqf.DOI: 10.15408/ajis.v15i2.2857